Reporting Excellent Transverse Piezoelectric and Electro‐Optic Effects in Transparent Rhombohedral PMN‐PT Single Crystal by Engineered Domains - Deng, Chenguang; Ye, Lianxu; He, Chongjun; Xu, Guisheng; Zhai, Qinxiao; Luo, Haosu; Liu, Youwen; Bell, Andrew J. (Advanced materials (Weinheim), 2021)
Transparent ferroelectric crystals with high piezoelectricity are challenging to build because of their complex structure and disordered domains in rhombohedral relaxor ferroelectrics. There are eight domains along the direction, which cause light scattering. In this study, perfect transparency is achieved along the [110] and [001] directions in [110]‐poled rhombohedral 0.72Pb(Mg1/3Nb2/3)O3‐0.28PbTiO3 (PMN‐PT) crystals, which have a high d31 value of 1700 pC N−1 and a high electro‐optic coefficient γ33 of 320 pm V−1. This implies that the [110]‐oriented rhombohedral PMN‐0.28PT crystal can realize the mode of transverse modulation, whereas the [001]‐oriented PMN‐0.28PT crystal is more suitable for the longitudinal mode. Through piezoresponse force microscopy (PFM), it is confirmed that the [110]‐poled rhombohedral PMN‐PT crystals form 71° layered domains, which are similar to the 109° layered domains of the [001]‐oriented transparent crystal. Combined with PFM and birefringence microscopy, the degradation of domains and thickness dependence of piezoelectricity provide clear evidence for the relationship between the engineered domain structures and piezoelectric properties, which should be considered in the design of piezoelectric or electro‐optic devices with excellent performance. This work enriches the research on ferroelectric domain engineering for excellent transparency and high piezoelectricity to provide new ideas for photoacoustic devices. Perfect transparency is achieved along the [110] and [001] directions in [110]‐poled rhombohedral PMN‐PT crystals, which have a high d31 value of 1700 pC N−1 and a high electro‐optic coefficient γ33 of 320 pm V−1. This implies that the [110]‐oriented rhombohedral PMN‐PT crystal can realize the mode of transverse modulation.